The French New Towns - Rubenstein, James M. (Book collections on Project MUSE., 2019)
At the time this book was published, new towns were cropping up as a matter of public policy in "advanced industrial countries," yet the United States abandoned this project and deemed new towns "inappropriate and impractical for the American situation." The purpose of this book is to inform planners and policy makers around the world about French new towns. It analyzes what French new towns tried to accomplish; the administrative, financial, and political reforms needed to secure implementation of the program; and the achievements of the new towns. The author's evaluation of French new towns is undertaken with an eye to international applicability. Chapter 1 examines the reasons for adopting a policy of new towns in France. Chapter 2 concerns the administrative structure by which new towns are built in France. Chapter 3 concentrates on major economic associations with new towns. Chapter 4 discusses the role of the private sector in the development of new towns. Chapter 5 examines the major accomplishment of the French new towns: the achievement of socially balanced communities. In the United States, new towns have been proposed as a means for integrating low-income families into suburbs that are otherwise closed to them. The French experience demonstrates that socially heterogeneous new communities can be developed, even within the framework of a market system, if a sufficiently high priority is placed on the effort